Using a Communicative Approach in Learning Speaking - Husni, Yunadil; Ratnasari, Lili (Strata Social and Humanities Studies, 2023)
This research aims to obtain an overview of the use of the communicative approach in learning to speak Indonesian at SMPN 3 Pantai Cermin, Solok Regency, in terms of (1) the use of the communicative approach in learning Indonesian, (2) the obstacles found by Indonesian language teachers in learning to speak Indonesian, (3) solutions carried out by teachers to overcome the obstacles that exist in implementing learning to speak Indonesian. Obtained using interview techniques, observation, recording, and documentation studies. This research is classified as descriptive research. The results of the research reveal that (1) Indonesian language teachers at SMPN 3 Pantai Cermin understand the communicative approach quite well and have used it in the learning process, and (2) the obstacles faced by Indonesian language teachers in learning to speak still exist. But, it can be overcome by using this approach. Communicative, (3) the solutions taken to overcome the obstacles faced by the informants vary, to make the obstacles faced as motivation for students who are reluctant and do not want to appear in front of the class to speak.